2017
DOI: 10.5152/tao.2017.2389
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and IL-1 β Cytokine Gene Polymorphism in Patients with Nasal Polyposis

Abstract: Objective: Nasal Polyp (NP) is a benign mass of the paranasal sinuses that protrudes into the nasal cavity. The exact underlying pathogenesis is not known. In this study we aimed to determine the genetic susceptibility of NP formation in relation to TNF-α-308 and IL-1β-511 promoter region gene polymorphisms. Methods:A total of 71 patients with NP with asthma (n=21) or without asthma (n=50) were taken as the study group, and 91 healthy volunteers were taken as the control group. Blood was gathered into EDTA-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…At the same time, a component of the inflammasome, GSDMD, is sheared and participates in the formation of cell membrane pores; the inflammatory mediators IL‐18 and Il‐1β can be released into the extracellular space through these pores 46 . As a result, pyroptosis can lead to an excessive inflammatory response, accumulation of inflammatory mediators and infiltration by inflammatory cells, finally leading to fever, low blood pressure and other clinical manifestations 47,48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a component of the inflammasome, GSDMD, is sheared and participates in the formation of cell membrane pores; the inflammatory mediators IL‐18 and Il‐1β can be released into the extracellular space through these pores 46 . As a result, pyroptosis can lead to an excessive inflammatory response, accumulation of inflammatory mediators and infiltration by inflammatory cells, finally leading to fever, low blood pressure and other clinical manifestations 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…※P < .05, compared with the LPS + WT groupspace through these pores 46. As a result, pyroptosis can lead to an excessive inflammatory response, accumulation of inflammatory mediators and infiltration by inflammatory cells, finally leading to fever, low blood pressure and other clinical manifestations 47,48. As shown in the present study, CC-5013 ameliorated pathological damages to the liver and kidneys in the ALF and AKI mouse model.…”
mentioning
confidence: 99%
“…These findings were partially in line with previous reports indicating that NKA expression or activity could be suppressed by SEB, LPS, IFN-γ, IL-1β, or TNF-α intervention on a variety of tissues and cells including rat intestinal mucosa [26], rat astrocytes [27], human intestinal xenografts [28], rat cardiac myocytes [29], and HepG2 cells (a human liver cancer cell line) [30], et al Previous studies have indicated the SEB and LPS could exacerbate inflammatory responses of HNECs in CRSwNP [31][32][33], thus, collectively, it can be surmised that NKA function in HNECs is impaired following SEB and LPS treatment, indicating that bacterial infection could trigger aggravation of inflammation via impairing NKA function in HNECs. In addition, type 1 IFN-γ, type 2 IFNs (IL-4 and IL-13), and IL-1β could also exert important roles in the inflammatory responses in CRSwNP [4,34,35]; therefore, it is reasonable to speculate that NKA function in HNECs is also impaired following type 1 IFN-γ, type 2 IFNs (IL-4 and IL-13), and IL-1β stimulation, indicating that these IFNs could also induce trigger inflammatory responses via impairing NKA function in HNECs.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that cell pyroptosis is closely related to inflammatory response waterfall and organ damage caused by sepsis. Also, excessive activation induced by cell pyroptosis causes the release of a large amount of IL-1β, which would lead to cause inflammatory storms and organ damage once again (Ismi et al, 2017;Cavaillon, 2018). COX-2 is an inducible enzyme with enhanced the expression in tissue injury and inflammation.…”
Section: Figurementioning
confidence: 99%